Peer Pressure: Social Interaction and the Disposition Effect - Heimer, Rawley Z. (Review of Financial Studies, 2016)
Social interaction contributes to some traders’ disposition effect. New data from an investment-specific social network linked to individual-level trading records builds evidence of this connection. To credibly estimate causal peer effects, I exploit the staggered entry of retail brokerages into partnerships with the social trading web platform and compare trader activity before and after exposure to these new social conditions. Access to the social network nearly doubles the magnitude of a trader’s disposition effect. Traders connected in the network develop correlated levels of the disposition effect, a finding that can be replicated using workhorse data from a large discount brokerage. Received September 8, 2015; accepted May 3, 2016 by Editor Stefan Nagel.